Features of personality trust of Russian and Indonesian students in terms of network activity - N. L. Sungurova; Yu. E. Akimkina; R. Adawiyah (Obrazovanie i Nauka, 2023)
Introduction. The process of modern youth’s cybersocialisation is caused by the digitalisation and the inclusion of information and communication technologies (ICT) in daily life. Network activity is a part of students’ socialisation. The interaction of student youth in the virtual space is conditioned by personality trust, which is revealed through the categories of trust in oneself, other users and the virtual world. The personality trust of students, as a belief in the reliability of other people and the world, regulates network activity and the life of society. Trends in the formation of personality trust in traditional and virtual space have similar prerequisites.Aim. The aim of the study is to identify the features of personality trust of Russian and Indonesian students in terms of network activity.Methodology and research methods. The study was conducted on the basis of the subject-personal approach. A set of methods was used: “Assessment of trust/distrust of a person in other people” (A. B. Kupreychenko) (the authors introduced an additional construct “virtual world”); “The study of trust/distrust of the individual in the world, other people, oneself”; “Questionnaire for the problematic use of social networks”; “Assessment of involvement in the use of ICT”.Results and scientific novelty. For the first time, personality trust is considered in the context of network activity in the framework of a comparative study of Russian and Indonesian students. Indonesian students tend to display personality trust in communication by accepting participants in network activity, in choosing more authoritative sources of information and participants with a positive reputation. Students from Russia trust reliable and credible sources and network users, basing on empathy and a similar worldview. The personality trust of students in the virtual world and network users is more pronounced among Indonesians, and trust in oneself is equally important for both groups of students. The Russian student youth is characterised by a low level of trust in the information on the network, in comparison with the Indonesian youth. General trends in the problematic use of technology have been identified, such as cognitive absorption, emotion regulation, and Internet addictive behaviour. Both groups of students prefer online communication and strive for open and effective relationships in the virtual space with like-minded people, for mutual assistance and unity.Practical significance. The results of studying the personality trust of Russian and Indonesian students in terms of network activity can be used to build open and productive relationships between young representatives of the countries, to organise psychological and pedagogical support for the socio-cultural adaptation of foreign students, to develop digital educational environment of an international university.